Bozena Nemcova's life from three points of view (Milos Urban, Frantisek Novotny, Lenka Lagronova) - Pajak, Aleksandra (Bohemica Olomucensia, 2018)
The paper employs Aby Warburg's concept of Nachleben to analyse Bozena Nemcova's figure. It concentrates on her images created after 1989 which constitute a sign of breaking the cultural taboo. In Urban's action novel, she is demythologized in the intermezzi that are ostensibly unrelated to the actual plot. Novotny's figuratively and literally "undresses" the writer, whereas Lagronova demonstrates the woman's tragedy as a victim of other people's desires.
Keywords: deheroisation; "second life"; cultural taboo; Bozena Nemcova; Milos Urban; Frantisek Novotny; Lenka Lagronova